Keterampilan Merajut Bagi Santri-Santri Rumah Tahfidz Al-Fazz - Susy Deliani; Siti Fatimah Zahara; Sri Muliatik; Mindalisma Mindalisma; Andi Syahputra Harahap (Fakultas Keguruan dan Ilmu Pendidikan UNIVA Medan, 2025)
This community service activity aims to improve knitting skills among students of Rumah Tahfidz Al-Fazz as an effort to develop creativity and economic independence. The main problem faced by the partner institution is the limited productive skills that can support students’ life skills beyond Qur’an memorization activities. The implementation method consisted of planning, training, mentoring, and evaluation stages. The training was conducted through the introduction of basic knitting concepts, tools and materials, fundamental knitting techniques, and hands-on practice in producing simple knitted products such as wallets and bags. The activity was carried out directly using a participatory approach to encourage active involvement of the students throughout the training process. The results showed that the students were able to understand basic knitting techniques and produce simple knitted products with a satisfactory level of neatness. In addition, the activity increased students’ creativity, self-confidence, and interest in entrepreneurship. In conclusion, knitting skills training is effective as a means of developing students’ life skills and has the potential to become a sustainable productive activity at Rumah Tahfidz Al-Fazz.